De Morgan's Laws (Logic)/Disjunction of Negations/Formulation 1

From ProofWiki
Jump to navigation Jump to search

Theorem

$\neg p \lor \neg q \dashv \vdash \neg \left({p \land q}\right)$


This can be expressed as two separate theorems:

Forward Implication

$\neg p \lor \neg q \vdash \neg \left({p \land q}\right)$

Reverse Implication

$\neg \left({p \land q}\right) \vdash \neg p \lor \neg q$


Proof

We apply the Method of Truth Tables.

As can be seen by inspection, the truth values under the main connectives match for all boolean interpretations.

$\begin{array}{|ccccc||cccc|} \hline \neg & p & \lor & \neg & q & \neg & (p & \land & q) \\ \hline T & F & T & T & F & T & F & F & F \\ T & F & T & F & T & T & F & F & T \\ F & T & T & T & F & T & T & F & F \\ F & T & F & F & T & F & T & T & T \\ \hline \end{array}$

$\blacksquare$


Sources